The dynamics of dislocation wall generation in metals and alloys under shock loading. (15th April 2015) - Rzhavtsev, E.A.; Gutkin, M.Yu.
Abstract : Two-dimensional discrete dislocation–disclination dynamics is applied to model the formation of dislocation walls in shock loaded metals and alloys. The dislocation walls are generated under an external stress impulse and the stress fields of pre-existed wedge disclinations distributed over the subgrain boundary. The case of an aluminum alloy is analyzed. It is shown that the typical shock duration is enough to complete the fragmentation process within the initial subgrain, and the necessary stress magnitude well agrees with experiments.